Emerging Carbon Capture Technologies in the Palm Oil Industry: A Review of Bioenergy and Carbon Capture Storage Approaches - Judijanto, Loso (Malikussaleh University, Aceh, Indonesia, 2025)
The accelerating impacts of climate change have heightened global interest in technologies that reduce greenhouse gas emissions from high-emission sectors such as agriculture and agri-processing. The palm oil sector is notably both a significant emitter and a promising avenue for decarbonization efforts, particularly through the integration of bioenergy systems and carbon capture technologies. This study aims to explore the current state of technological development in carbon capture and storage (CCS) and bioenergy applications within the palm oil industry and to identify the major challenges and opportunities that shape their implementation between 2021 and 2025. This investigation employs a qualitative design through the SLR method, structured in accordance with the PRISMA framework for transparency and rigor in literature synthesis. Data were collected from the ScienceDirect database using a refined combination of Boolean search terms. A total of 1,088 articles were initially identified and screened through a multistage filtration process that included relevance checks, publication period constraints, research article type, and open-access availability. This process resulted in 36 articles that met all inclusion criteria and were analyzed further. Data were synthesized through thematic analysis to classify technological pathways, assess implementation trends, and evaluate technical, economic, and policy-related barriers. Findings reveal that while bioenergy from palm oil residues is widely adopted, CCS deployment remains minimal due to cost, infrastructure, and regulatory limitations. The study concludes that targeted policy support and innovation are essential to scaling up carbon management in this sector. Future research should prioritize pilot demonstrations and interdisciplinary assessments of CCS integration feasibility.